HETEROSIS FOR YIELD AND ITS CONTRIBUTING ATTRIBUTES IN BRINJAL (SOLANUM MELONGENA L.) - A. Y. MAKANI; A. L. PATEL; M. M. BHATT; P. C. PATEL (The Bioscan, 2013)
A study was conducted in brinjal to estimate the magnitude of heterosis for yield and its eleven yield components. 28 F1 hybrids generated by half diallel crosses of eight pure diverse parent and these F1s along with 8 parents were evaluated in a randomized block design with three replication at Research farm of Main Vegetable Research Station at Anand, Gujarat (India). Appreciable heterosis was found over mid, better and standard parent for all the traits studied in desirable direction. In order of merit F1 hybrids AB-07-08 x GP-180 (136.39%), AB-07-08 x KS331 (102.20%) and NDB-18 x AB-07-08 (97.63%) were observed significant heterosis over mid parent while the maximum heterobeltiosis (better parent heterosis) for fruit yield per plant was exhibited by the hybrid AB-07-08 x GP-180 (125.78%) followed by NDB-18 x AB-07-08 (86.25%) and Doli-5 x GP-180 (72.09%). In case of standard heterosis, significant and positive heterosis over standard check GBL-1 for fruit yield per plant was observed in hybrid GBL-1 x KS-331 (50.41%) followed by AB-07-08 x KS-331 (43.53%) and Doli-5 x GBL-1 (42.59%). The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1s as well as commercial exploitation of heterosis in brinjal.